Cloning and characterization of a Drosophila serotonin receptor that activates adenylate cyclase. - Witz, P (1990)
Using a strategy based on nucleotide sequence homology between genes encoding receptors that interact with guanine nucleotide-binding proteins, we have isolated Drosophila genomic and cDNA clones encoding a functional serotonin receptor (5HT-dro receptor). This protein is expressed predominantly in Drosophila heads and exhibits highest homology with the human 5HT1A receptor. The predicted structure of the 5HT-dro receptor reveals two unusual features: (i) eight putative transmembrane domains instead of the expected seven and (ii) a Gly-Ser repeat that is a potential glycosaminoglycan attachment site. When stably introduced into mouse NIH 3T3 cells, the 5HT-dro receptor activates adenylate cyclase in response to serotonin and is inhibited by serotonin receptor antagonists such as dihydroergocryptine. The 5HT-dro receptor or closely related receptors might be responsible for the serotonin-sensitive cyclase that has been suggested to play a role in learning and modulation of circadian rhythm in a number of invertebrate systems.